Entrepreneurship - Hisrich, Robert D.; Peters, Michael P.; Shepherd, Dean A. (McGraw-Hill/Irwin, 2005)
Entrepreneurship, by Hisrich, Peters and Shepherd is intended for the undergraduate and graduate courses in entrepreneurship and has been designed to instruct students on how to formulate, plan, and implement a new venture. Students are exposed to detailed descriptions of 'how to' embark on a new venture in a logical manner. Actual case studies and entrepreneur profiles help illustrate successful and not-so-successful ventures.